BASES PRELIMINARES PARA UNA PERSPECTIVA HISTÓRICA SOBRE LA INVESTIGACIÓN EN LAS QUILCAS O EL ARTE RUPESTRE PERUANO - Echevarría López, Gori Tumi (2017)
This article, adapted from a lecture, outlines the bases for a historiography of the rock art research in Peru, using as division point the main intellectual or theoretical tendencies that have surrounded this investigation. The text highlights five major stages of development regarding the study of rock art, which do not constitute a linear course of a continuous academic development, but a fragmented history characterized by moments of remarkable scientific advances and at the same time of strong intellectual regression.